Sick from what? Trauma during the SARS-CoV-2 pandemic - Dustin Rawlinson; Jorge Vega; Lawrence Lottenberg; Robert Borrego; Mario Rueda; Faris Azar (Trauma Case Reports, 2021)
Background: We present the case of two brothers with identical mechanisms of injury presenting simultaneously, one with SARS-Cov-2 respiratory failure and the other in hemorrhagic shock. Summary: Healthcare globally and in the United States met novel challenges during the unprecedented severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) health crisis. The effect of SARS-CoV-2 on hospital and health care delivery systems has been widely reported. Elective surgical procedures were suspended; however, trauma and acute care services remained active and faced unique challenges during this pandemic. Trauma patients by their nature of injury require rapid assessment and treatment to include invasive emergency operations. Not only do trauma centers have to adapt to limited resources and new procedures limiting exposure, they are also met with the confounding issue of trauma patients concomitantly presenting with SARS-CoV-2 respiratory illness. Conclusion: Trauma care providers must now contend with SARS-CoV-2 on the differential for patients presenting with trauma. This is demonstrated by our case of two brothers with identical mechanisms of injury presenting simultaneously, one in shock from respiratory failure and the other hemorrhagic.